(untitled) (International Journal of Communication Systems and Network Technologies, 2020)
We are slowly reaching the age of electric vehicles within the last few years research for electric vehicles has significantly increased. The major issue behind the mass use of electric vehicle is the battery charging time and lack of charging station. So, here we proposed “Regenerative braking system”. When we switch on the power supply the wheel starts propelling, but due to some interruption when brakes are applied small amount of voltage will be generated. Further that energy will be stored in the battery which will be given to a load.